Is STN Neuromodulation of Focal Motor Seizures Ready for Prime Time?. Issue 2 (March 2021) - King-Stephens, David
Subthalamic Nucleus Stimulation Modulates Motor Epileptic Activity in Humans. Ren SL, Yu T, Wang D, et al. Ann Neurol . 2020;88(2):283-296. doi:10.1002/ana.25776 . Objective: Pharmacorefractory focal motor epileptic seizures pose a significant challenge. Deep brain stimulation is a recently recognized therapeutic option for the treatment of refractory epilepsy. To identify the specific target for focal motor seizures, we evaluate the modulatory effects of the subthalamic nucleus (STN) stimulation because of the critical role of STN in cortico–subcortical motor processing. Methods: Seven patients with epilepsy with refractory seizures who underwent chronic stereoelectroencephalography monitoring were studied in presurgical evaluation. Seizure onset zone was hypothesized to be partially involved in the motor areas in 6 patients. For each patient, 1 electrode was temporally implanted into the STN that was ipsilateral to the seizure onset zone. The cortical–subcortical seizure propagation was systemically evaluated. The simultaneously electrophysiological responses over distributed cortical areas to STN stimulation at varied frequencies were quantitatively assessed. Results: We observed the consistent downstream propagation of seizures from the motor cortex toward the ipsilateral STN and remarkable cortical responses on motor cortex to single-pulse STN stimulation. Furthermore, we showed frequency-dependent upstream modulatory effect of STN stimulation on motor cortex specifically. In contrast to the enhanced effects of low-frequency stimulation, high-frequency stimulation of the STN can significantly reduce interictal spikes, high-frequency oscillations over motor cortex disclosing effective connections to the STN. Interpretation: This result showed that the STN is not only engaged in as a propagation network of focal motor seizures but STN stimulation can profoundly modulate the epileptic activity of motor cortex in humans, suggesting a mechanism-based alternative for patients suffering from refractory focal motor seizures.